Sustained increase in the use of alcohol-based hand rubs in Finnish long-term care facilities - Rummukainen, Maija-Liisa; Jakobsson, Äino; matsinen, Maire; Karppi, Pertti; Järvenpää, Salme; Lyytikäinen, Outi (International Journal of Infection Control, 2011)
Long-term care facilities (LTCFs) may serve as a reservoir for multi-resistant bacteria. Hand disinfection with alcohol-based rubs is a simple tool for controlling cross-contamination between patients and preventing healthcare-associated infections. Our aim was to promote the use of alcohol-based hand rubs. A multidisciplinary team (an infectious disease consultant, an infection control nurse, and a geriatrician) visited all LTCFs (n=123) for elderly persons in the Central Finland Healthcare District (population 265 000) between September 2004 and October 2005. In each unit, head nurses and often also general practitioners answered structured questions concerning the monthly amount of alcohol-based hand rubs used in liters and patient days. The facility environment was evaluated, especially the opportunities for hand disinfection and new locations for additional hand rub containers were proposed. During 2006-2008, three postal surveys including feedback were conducted annually. A total of 119 units with around 3500 residents participated in all four steps (a site visit and three postal surveys). The total amount of hand rub used increased by 70%, from the mean (SD) of 7.3 (5.1) liters/1000 patient days on the baseline visit to 12.4 liters (14.9) in 2008. The multidisciplinary team succeeded in promoting hand hygiene in LTCFs, which was sustained over the three-year follow-up. Continuous training is needed to preserve the positive trend and direct observations to assess whether hand hygiene is performed correctly and at the right time.